Tantangan Tata Kelola Kebersihan Lingkungan di Wilayah Perbatasan: Studi Kasus Pengelolaan Sampah Desa Sulauwangi - Dean Anugrah; Deco Megantara; Andini Aprilia; Yunita Eka Rizki; Muhammad Adit Husnaen (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Environmental sanitation management in border areas often faces complex obstacles due to geographical isolation and limited basic infrastructure. This study aims to analyze the current waste management governance patterns and identify the main challenges in maintaining environmental cleanliness in Sulauwangi Village, a rural border area. This research used a qualitative approach with a case study method. Data were gathered through in-depth interviews, field observations, Focus Group Discussions (FGD), and documentation studies. The results indicate that the waste management pattern in Sulauwangi Village remains conventional without source sorting, where waste disposal is dominated by open burning and indiscriminate dumping. The main governance challenges fall into four dimensions: institutional (absence of village regulations and management bodies), social (low ecological awareness among residents), economic (minimal village budget allocation and lack of retribution), and infrastructure (lack of temporary shelters and accessibility barriers for waste collection vehicles). This study recommends the formulation of village sanitation regulations, the establishment of local BUMDes/community-based management institutions, and cross-sectoral collaboration between local governments and the community to establish sustainable environmental governance in border areas.